The Syntax of Null Subjects. (11th March 2014) - Kučerová, Ivona
Abstract This paper presents a case study of a group of null‐subject languages in which there is referential pro that fails to satisfy the Extended Projection Principle (EPP) because it does not move to Spec, TP. Thus, this group of null‐subject languages contrasts with the more familiar type of null‐subject languages, such as Romance and Greek, in which the EPP is always satisfied either by pro or a D‐feature in T. To account for the syntactic distribution of null subjects in these languages, some form of the EPP requirement must be taken into account. This empirical observation has consequences for the typology of null‐subject languages and contributes to the growing literature showing that the [± null‐subject] parameter might need to be refined in order to capture the continuum of types of null‐subject languages attested crosslinguistically.